Mediterranean Quercus suber wooded grasslands risk disappearance: New evidences from Sardinia (Italy) - Rossetti, Ivo; Bagella, Simonetta (Forest Ecology and Management, 2014)
Wooded grasslands are the most widespread agro-forestry systems in Europe, and are included in the Natura 2000 network due to their importance in biodiversity conservation. Similar to many man-made systems, long-term wooded grasslands conservation depends on sustainable use practices. Regeneration of the tree layer is indispensable to assure wooded grassland maintenance. Several studies in Spanish dehesas and Portuguese montados generated concerns regarding the long-term conservation of these agro-silvo-pastoral systems. In the present study, we tested if tree regeneration issues documented for the Iberian Peninsula also affected wooded grasslands located in another Mediterranean area inside and outside Natura 2000 network. The size structure of Quercus suber L. stands, and the abundance and height of seedlings and saplings were determined at farm and landscape scales, in grazed, grazed and tilled wooded grasslands, and non-grazed woodlands to test the compatibility of management type for tree regeneration. A frequency model of size structure was calculated to estimate the probability of cork oak stand survival in a medium and long term time period. New evidences of a generalised absence of regeneration in grazed wooded grasslands emerged from all the study sites. Some management practices are indicated for the long-term conservation of the habitat.
Keywords: Grazing; Habitat 6310; Natura 2000; Predictions; SIZE STRUCTURE; Tillage

Is tree shelter protection an effective complement to weed competition management in improving the morpho-physiological response of holm oak planted seedlings? - Ceacero, Carlos J; Navarro-cerrillo, Rafael M; Díaz-Hernández, José Luis (iForest - Biogeosciences and Forestry, 2014)
Weed control is a key aspect that influences seedling response in newly-established plantations. Tree shelter protection may be an effective complement to weed control with a positive effect on the overall response of seedlings. Our study focused on assessing the morpho-physiological response of Holm oak (Quercus ilex L. ballota [Desf.] Samp.) plantations to weed control and individual protection as a combined cultural technique on a cropland site in southern Spain. The weed control treatments (cultivation, herbicide and mulch) were also applied in combination with tree shelters. Morpho-physiological variables including survival, aerial and root morphology, water potential, gas exchange and chlorophyll fluorescence were monitored over a 2-year period. Results showed that weed competition management treatments improved the seedling survival rate compared to the control treatment. Moreover, shelter was associated with a greater height growth. At early stages of establishment, and particularly under combined treatments, all plants invested more resources in their aerial parts than in their root system. Seedlings did not regulate water loss as a result of water stress, contrary to what would be expected in Mediterranean areas. Under all treatments, especially those combined with tree shelters, seedlings took up to 2 years to achieve morpho-physiological adaptation (i.e. height and diameter growths, water stress behavior) to site conditions. In addition, tree shelters promoted an increase in net photosynthesis compared to non-shelter treatments during the winter period. The tree shelters also limited the emergence of photo-inhibition phenomena in seedlings so that plants under combined treatments showed greater photo-chemical efficiency. Thus, this study supports the effectiveness of tree shelter protection as a complement to weed control treatments. More specifically, it suggests that combining individual protection (shelter) and weed control around seedlings is an interesting technique for reforestation of forest ecosystems in Mediterranean areas.
Keywords: Mulch; Oxyfluorfen; photoinhibition; photosynthesis; Tillage; tree shelter

Effects of long-term management practices on grassland plant assemblages in Mediterranean cork oak silvo-pastoral systems - Bagella, Simonetta; Salis, Lorenzo; Marrosu, Gian Marco; Rossetti, Ivo; Fanni, Stefania; Caria, Maria Carmela; Roggero, Pier Paolo (PLANT ECOLOGY, 2013)
The assessment of the effects of long-term management practices is relevant in understanding the current patterns of plant assemblages in semi-natural ecosystems. We hypothesized that the variety of management practices across different farming systems under the same ecological conditions directly and indirectly shapes these patterns via the long-term changes induced in soil features. The aims of this paper were to evaluate the influence of two sets of variables describing long-term management practices and soil features on plant assemblages and their importance in the context of Mediterranean silvo-pastoral systems. The analysis of variance revealed that richness and grazing value were not affected at all by grazing livestock species and soil tillage frequency and that they both showed relatively high absolute values for the specific context under study. Trifolium subterraneum was a key species in contributing to grassland grazing value and habitat biodiversity. The Canonical Correspondence Analysis highlighted the influence of management practices and soil features on plant assemblage composition, which was significantly affected by grazing livestock species and stocking rate and by soil pH and K content. The Redundancy Analysis showed that soil pH and related features were in turn affected by stocking rate, supporting our hypothesis that management practices influenced plant assemblage composition directly and indirectly via their long-term effects on soil features. The results also highlighted that a systemic analytical perspective applied at a grazing system scale can be effective in addressing sustainable grassland management issues in Mediterranean silvo-pastoral systems.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: grazing systems; soil features; Stocking rate; Tillage; Trifolium subterraneum

Stratification ratio of soil organic C, N and C:N in Mediterranean evergreen oak woodland with conventional and organic tillage - Corral-Fernández, R.; Parras-Alcántara, L.; Lozano-García, B. (Agriculture, Ecosystems & Environment, 2013)
TheMediterraneanevergreenoakwoodland(MEOW-dehesa)is themostwidespreadagroforestry system in Mediterranean Europe and integrates forestry, agricultural and livestock practices. The MEOW-dehesa is a grazing system with evergreen Quercus ilex spp. ballota. It is characterized by the conservation of forest oaks (Quercus spp.) and provides environmental beneﬁts such as carbon capture and storage in soils. The effect of conventional tillage (CT) and organic tillage (OT) on the distribution of soil organic carbon (SOC), total nitrogen (TN) and C:N ratios has not been well documented in the MEOW-dehesa. The objective of this paper is to study these parameters in the MEOW-dehesa in two soil types (Leptosols and Cambisols) and two management systems, OT for 20 years and CT. The stratiﬁcation ratio (SR) of SOC, TN and C:N ratio is also evaluated. An analysis is performed on 85 soil proﬁles over the 2005–2009 period in southern Spain. The SR of SOC in Cambisols was greater under OT than CT, ranging from 1.25 to 1.42 and from 1.3 to 1.6 under CT and OT, respectively. The SR of TN for 0–20.9 cm, 20.9–55.5 cm and 55.5–102.1 cm depth was greater under OT than under CT. The OT also increased the stratiﬁcation of the C:N ratio compared to CT.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: C:N ratio; Dehesa; Soil organic carbon; Stratiﬁcation ratio; Tillage

Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi as indicators of land-use severity in managed woodlands dominated by Quercus suber — a case study from southern Portugal - Azul, Anabela Marisa; Castro, Paula; Sousa, José Paulo; Freitas, Helena (Canadian Journal of Forest Research, 2009)
We assessed the impacts of current management practices used to control shrub strata in Portuguese oak woodlands dominated by Quercus suber L. (montado) on fruiting diversity and abundance of ectomycorrhizal-forming fungi (ECMF) and saprobic fungi. Fruit bodies were collected over four fruiting seasons in 16 plots (20 m × 20 m) selected in a montado landscape with extensive silvopastoral exploitation. A total of 9484 fruit bodies were found in 171 taxa (74 ECMF, 96 saprobic, and 1 parasitic). Our results show that shrub density control by permanent grazing or by cutting practices followed by soil tillage leads to lower fruiting production and greater changes in taxa composition, particularly for ECMF fruit bodies, than cutting practices without soil tillage. Principal response curve analysis showed that ECMF reacted more sensitively to these practices, in particular Laccaria laccata, Hebeloma cistophilum, Russula cyanoxantha, Cortinarius trivialis, and Lactarius volemus. We also observed that shrub cutting without soil tillage allowed ECMF fruiting to recover to predisturbance levels after 3 years. Our data imply that fruit bodies were useful indicators for assessing the severity of the effects of different land-use practices applied in montado areas on soil fungal populations.
doi: 10.1139/X09-148
Keywords: diversity; fruiting patterns; fungi; montado (voyant); shrub management; Tillage

Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi as indicators of land-use severity in managed woodlands dominated by Quercus suber — a case study from southern Portugal - Azul, Anabela Marisa; Castro, Paula; Sousa, José Paulo; Freitas, Helena (Canadian Journal of Forest Research, 2009)
We assessed the impacts of current management practices used to control shrub strata in Portuguese oak woodlands dominated by Quercus suber L. (montado) on fruiting diversity and abundance of ectomycorrhizal-forming fungi (ECMF) and saprobic fungi. Fruit bodies were collected over four fruiting seasons in 16 plots (20 m × 20 m) selected in a montado landscape with extensive silvopastoral exploitation. A total of 9484 fruit bodies were found in 171 taxa (74 ECMF, 96 saprobic, and 1 parasitic). Our results show that shrub density control by permanent grazing or by cutting practices followed by soil tillage leads to lower fruiting production and greater changes in taxa composition, particularly for ECMF fruit bodies, than cutting practices without soil tillage. Principal response curve analysis showed that ECMF reacted more sensitively to these practices, in particular Laccaria laccata, Hebeloma cistophilum, Russula cyanoxantha, Cortinarius trivialis, and Lactarius volemus. We also observed that shrub cutting without soil tillage allowed ECMF fruiting to recover to predisturbance levels after 3 years. Our data imply that fruit bodies were useful indicators for assessing the severity of the effects of different land-use practices applied in montado areas on soil fungal populations.
doi: 10.1139/X09-148doi: 10.1139/X09-148The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: diversity; fruiting patterns; fungi; montado (voyant); shrub management; Tillage

PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS - Ambiente, Ministerio D E Medio; NICOLÁS PERAGÓN, J L; DOMÍNGUEZ LERENA, S; HERRERO SIERRA, N; VILLAR- SALVADOR, P (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.
Keywords: Acorn seeding; Holm oak; microclimate; Reforestation; Tillage

PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS - Ambiente, Ministerio D. E. Medio; NICOLÁS PERAGÓN, J. L.; DOMINGUEZ LERENA, S.; HERRERO SIERRA, N.; VILLAR- SALVADOR, P. (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Acorn seeding; Holm oak; microclimate; Reforestation; Tillage